Anatomical Characters Used for Defining Five Species of Nepenthes from Bangka Belitung Islands, Indonesia - Sakina Rizqiani; Nunik Sri Ariyanti; Sulistijorini Sulistijorini (Journal of Tropical Life Science, 2018)
Anatomical structures may vary among the species of Nepenthes. Therefore, the anatomical characters apparently could be used for supporting the morphological characters in identifying species. This study aimed to seek a valuable anatomical character for identifying and defining five species of Nepenthes occur in Bangka Belitung Islands. Samples of leaves, pitchers and its lids of Nepenthes gracilis, Nepenthes mirabilis, Nepenthes ampullaria, Nepenthes rafflesiana, and Nepenthes reinwardtiana were collected and prepared for paradermal and transverse section of microscope slides. The results showed that the anatomical characters of the leaves, pitchers and lids from these five species of Nepenthes could be used for differentiating five species Nepenthes observed. The absence of nectary gland at the abaxial of pitcher lids of N. gracilis and N. ampullaria separate them from others species. The leaf epidermis of these two species have different cell wall. The length of lunate cells at the inner surface of upper half pitchers are comparable for identifying the pitchers of N. mirabilis from those of N. reinwardtiana.Â The presence of crystal at the parenchymal tissue of pitcher differentiate N. rafflesiana from the four others.Â In this research, the identification key for Nepenthes from Bangka Belitung Islands based on the anatomical character was presented.